Spin polarization in Cu2MnSn Heusler alloy produced by melt-spinning. (June 2017) - Obaida, M.; Galdun, L.; Ryba, T.; Komanicky, V.; Saksl, K.; Durisin, M.; Kovac, J.; Haskova, V.; Szabo, P.; Vargova, Z.; Varga, R.
Abstract: We report on magnetism, transport and spin polarization characteristics of the melt-spun Cu2 MnSn alloy prepared by the rapid quenching technique. The as- cast ribbons showed a relatively well ordered chemical composition (Cu = 50.4%, Mn = 27.1%, Sn = 22.5%). The structural characterization by using X-ray diffraction shows L21 /B2 crystalline structure with the lattice parameter a  = 6.196 Å. The magnetic and transport measurements show a metallic behavior with the Curie temperature of 530 K and reveal anisotropic character with the easy magnetization plane parallel with respect to the ribbon plane. As-cast Cu2 MnSn ribbons show the spin polarization measured by using Andreev reflection technique within the range 68–75%. Highlights: Single phase Cu2 MnSn Heusler alloy with well-defined anisotropy was produced in a single production step. It exhibit high Curie temperature and well defined anisotropy with the easy plane parallel with the ribbon plane. The spin polarization reaches values up to 75% due to strong asymmetry in the minority and majority density of state.